Evaluasi Geometrik dan Perilaku Pengendara di Jembatan Ketiwon Jalan Werkudoro - Hadi, Suprapto; Yuanita, Amelia Ratna; Inayati, Nabilla Rahma; Huda, Rachmad Miftah; Ramadhani, Restu; Purwanto, Edi (Jurnal Talenta Sipil, 2025)
Werkudoro Road in Tegal City is classified as a Class III road functioning as a secondary collector with a design speed of 40 km/h. One of the accident-prone locations along this route is at the Ketiwon Bridge. This study aims to assess the conformity of geometric road elements, specifically the horizontal and vertical alignments, with applicable technical standards, and to analyze their relationship with vehicle speed and driver behavior. A quantitative approach was applied, involving data collection through GNSS-based geometric measurements, vehicle speed surveys, and observations of traffic violations. The analysis revealed that the average operational speed reached 44 km/h, exceeding the designated design speed. The curve radius on the observed segment is 94 meters, which falls below the minimum required standard of 159 meters. Although the vertical gradient of 5.28% and the vertical curve length of 68.90 meters remain within the critical slope limit, the available stopping sight distance is only 82.50 meters—significantly lower than the required 182 meters. Based on these findings, several geometric elements of the road do not comply with existing standards and may compromise traffic safety. Therefore, improvements such as the installation of warning signs, enforcement of speed limits, and enhanced driver education are recommended to mitigate potential risks.